A CD24+CD271+ melanoma cancer stem cell possesses hybrid characteristics of its single marker counterparts and promotes invasion and therapeutic resistance - Olivia Knowles; Patricio Doldan; Isabella Hillier-Richardson; Sophia Lunetto; Stephanie Lunt; Gehad Youssef; Luke Gammon; Ian C. Mackenzie; Michael P. Philpott; Hasan Rizvi; Daniele Bergamaschi; Catherine A. Harwood; et al. (BMC Biology)
Abstract Background An important role for phenotype switching has been demonstrated in metastasis and therapeutic resistance of both melanoma and epithelial tumours. Phenotype switching in epithelial tumours is driven by a minority cancer stem cell (CSC) sub-population with lineage plasticity, but such a sub-population has not been identified in melanoma. We investigated whether cell surface markers used to identify CSCs in epithelial tumours could identify a CSC sub-population with lineage plasticity in melanoma. Results We identified a CD24+CD271+ minority sub-population in melanoma that possesses the stem cell characteristics of lineage plasticity and self-renewal. This population displayed hybrid characteristics, combining the attributes of discrete CD24+CD271- and CD24-CD271+ cellular sub-populations but with heightened sphere formation, lineage plasticity, migratory ability and drug resistance over its single-marker counterparts. CD24+CD271- and CD24+CD271+ stem cell sub-populations were observed in 10% of human melanomas, mainly at the invasive front. They were also found in human tumour scRNAseq datasets, where they expressed genes associated with stem cells and therapeutic resistance. The CD24-CD271+ sub-population, on the other hand, shared expression of epithelial-mesenchymal transition (EMT) genes with the CD24+CD271+ sub-population. Conclusions The lack of CD24+CD271- and CD24+CD271+ stem cells in the majority of human melanoma specimens led us to conclude that they may be dispensable for melanoma progression. Nevertheless, the enhanced sphere formation, lineage plasticity, migratory ability and drug resistance of the CD24+CD271+ sub-population may signal a contextual requirement for these stem cells when melanomas face challenging environments both clinically and in experimental systems.